Leucine-rich repeat neuronal 1 as a prognostic indicator and functional modulator in breast cancer - Wang, Jiaxin; Zhou, Xiqian; Ping, Ding; Lu, Meiling; Zhang, Yue; Song, Hongming; Zhao, Junyong; Li, Dengfeng (Frontiers in Oncology, 2025)
IntroductionAdvanced breast cancer remains a major therapeutic challenge with high mortality rates. While leucine-rich repeat (LRR) proteins play roles in various cancers including breast cancer, their specific functions are still underexplored. This study aimed to address this research gap by focusing on the leucine-rich repeat neuronal (LRRN) family, with the goal of clarifying their expression, clinical value, and prognostic significance in breast cancer—particularly LRRN1 in advanced cases.MethodsTo investigate the expression of LRRN family members in breast cancer, this study utilized public databases including TCGA-BRCA, GEO, and UALCAN. It further analyzed the clinical value of these LRRN family members and specifically identified the prognostic significance of LRRN1 in advanced breast cancer cases. Functional assays (assessing proliferative, migratory, and invasive capabilities of cancer cells) were conducted to evaluate LRRN1’s biological effects. Additionally, WGCNA, GO analysis, KEGG analysis, and western blotting were employed to verify the molecular pathways impacted by LRRN1.ResultsLRRN1 was found to be significantly downregulated in advanced breast cancer tissues compared to normal tissues (p < 0.001). Moreover, high LRRN1 expression correlated with better disease-free survival (DFS) in advanced breast cancer patients (HR=0.755, 95% CI: 0.617–0.923, p < 0.01). Functional assays revealed that LRRN1 suppresses cancer cell metastasis (without affecting cancer cell proliferation) (p<0.01). Results from WGCNA, GO, KEGG analyses, and western blot confirmed that LRRN1 impacts the Wnt signaling pathway (p<0.05). Additionally, LRRN1 may activate γδ T cells and resting dendritic cells, regulate the M1/M2 macrophage balance in the tumor microenvironment (p<0.001), and mediate the efficacy of certain tyrosine kinase inhibitors (TKIs) (p<0.001).DiscussionOverall, LRRN1 emerges as a promising prognostic indicator and functional mediator in advanced breast cancer. It potentially exerts its effects by influencing the Wnt signaling pathway and regulating immunotherapy responses. However, the specific mechanisms underlying LRRN1’s actions, as well as its potential clinical applications, still require further exploration to fully translate these findings into clinical practice for advanced breast cancer treatment.